Navigating Reputation and Surviving Online Defamation - Answendy, Putri Riska (Center for Law and Responsible Business Studies, 2025)
In the digital age, reputation is more vulnerable than ever due to the rapid dissemination of information across online platforms. With the exponential growth of data flows globally, a single negative online review can significantly damage the credibility and success of professional service providers, such as lawyers and doctors. This essay explores the complex intersection between online reviews, reputation, and defamation. It questions whether businesses, particularly professional service providers, should be allowed to sue for defamation in response to harmful online reviews. Drawing on both normative theories and real-world examples, this article examines the evolving definition of reputation, the legal standards of defamation, and how digital platforms complicate traditional legal frameworks. The analysis is supported by statistical evidence from Australia, which shows a substantial increase in digital defamation cases over the past decade. Additionally, this article delves into the motivations behind online reviews and their growing influence on consumer behaviour. Anonymity in online reviews, while protecting users, also raises concerns over accountability. This article argues for a balanced approach that upholds freedom of expression while protecting professional reputations from unjustified harm. Ultimately, it advocates for clearer legal standards and improved digital literacy to navigate defamation in the online era.